THEORETICAL REVIEW OF EVIDENCE-BASED PRACTICES OF PSYCHOLOGICAL REHABILITATION OF THE POPULATION DURING WAR (Psychology Travelogs, 2025)
The article presents a theoretical review of evidence-based practices of psychological rehabilitation for the population affected by war. The relevance of this study arises from the large-scale psychotraumatization of Ukrainian citizens caused by combat operations, forced displacement, loss of relatives, and destruction of homes. The purpose of the research is to systematize and analyze the most effective evidence-based methods of psychological support whose efficacy has been confirmed by international studies. The article examines the cognitive-behavioral therapy (CBT), trauma-focused CBT, eye movement desensitization and reprocessing (EMDR), narrative exposure therapy (NET), group interventions, psychoeducational programs, resilience training, and hypnotherapy. Their effectiveness in reducing symptoms of post-traumatic stress disorder, anxiety, depression, and other war-related psychological consequences is summarized. Special attention is given to the integration of these approaches into national mental health and social support systems. The article also emphasizes the necessity of adapting evidence-based practices to the Ukrainian sociocultural context and improving the professional training and supervision of specialists. It highlights the importance of developing flexible formats of psychological assistance, such as online counseling, mobile psychological teams, and the use of digital technologies in rehabilitation. The authors argue that digital tools, including online platforms and mobile applications, can expand access to psychological help even in wartime conditions. The integration of psychological and cultural interventions, such as art therapy and community-based activities, is discussed as an additional resource for collective resilience and postwar recovery. The study concludes that evidence-based practices represent a crucial foundation for effective psychological rehabilitation, restoration of social functioning, and enhancement of personal and societal resilience in postwar Ukraine.
Keywords: psychological rehabilitation; war; evidence-based practices; post-traumatic stress; cognitive-behavioral therapy